PENGENALAN PEMBAYARAN PAJAK MENGUNAKAN E-FILLING PADA MASYARAKAT DI PERUM CENTRA PARK KOTA BATAM - Tipa, Handra; Yusuf, Muhammad; Mulawarman, Mulawarman; Yuliadi, Yuliadi (Jurnal Pengabdian Cendikia Nusantara, 2024)
The development of information technology has encouraged the modernization of the taxation system, including the implementation of e-filing which offers efficiency and convenience in tax reporting. However, there are still many people, especially in Perum Centra Park, Batam City, who are not familiar with this system, so an introduction and training effort is needed to improve the understanding and use of e-filing in tax reporting.This community service aims to introduce the tax payment system using e-filing to residents of Perum Centra Park, Batam City. The method used in this activity focuses on developing participants' skills and knowledge through a combination of formal training and coaching tailored to individual needs. The activity begins with two days of intensive training (May 18-19, 2024), followed by a pre-test to measure participants' initial knowledge of E-Filling. Based on the pre-test results, the speaker then delivered coaching material tailored to the participants' abilities, supported by equipment such as laptops, LCD projectors, pre-test questions, and jobsheets, and evaluated based on predetermined achievement indicators. Community service activities have been successfully carried out with one meeting on April 21, 2024, focusing on the presentation of material on tax payments using E-filing to residents of Perum Centra Park Batam City. Despite facing some obstacles such as difficulty in aligning schedules and noisy location conditions, the training successfully covered various important aspects of e-Filing, including understanding, preparation, usage process, data security, as well as its benefits for MSMEs, which are expected to improve efficiency, transparency, and compliance in tax reporting. The introduction of e-filing at Perum Centra Park Batam City has the potential to improve tax compliance and efficiency of the tax system, supporting sustainable development.